FAKTOR PELAKSANAAN PIJAT BAYI DI RUANG NIFAS - Ketut L. Aryati; Esti Yunitasari; Retnayu Pradanie (Universitas Airlangga, 2014)
Introduction: The newborn or neonate is a baby who must meet a number of developmental tasks to obtain and maintain their own physical growth and development as separate from the mother's body. Various factors can affect growth and development in infants, one factor was common stimulation for infants is tactile stimulation in the form of massage such as baby massage. The infant massage is able to provide a sense of security, creating emotional and social relationship between mother and baby. This study was aimed to investigate factors correlating with the implementation of infant massage in the postpartum ward of Kupang Police Hospital.Method: The study design was descriptive cross sectional analytic approach. The independent variables in this study were maternal knowledge, maternal beliefs, health resources, support health workers and family support. The dependent variable in this study was the implementation of infant massage. The samples in this study were 15 mothers giving birth in the postpartum ward of Kupang Police Hospitals and entered in the category inclusion. Retrieval of data through questionnaires administered to the mother postpartum researchers at day 2 and day 3 postpartum.Result: Based on the results of statistical tests Spearman Rho p<0.05 then H1 was accepted in the study of maternal knowledge relations p=0.015 (r= 0.612 ), maternal confidence p =0.000 (r=0.866), health resource p=0.018(r =0.600), support health workers p=0.000 (r =0.873), and family support p=0.810 ( r = -0.068 ).Discussion: It can be concluded that there was a strong relationship between maternal knowledge and health resources to the implementation of infant massage and also there was a very strong relationship between maternal confidence and support of health workers with the implementation of infant massage. There needs to be more research on the role of health workers in providing health education on infant massage as supportive-educative system according to Orem's theory.